ANALISIS KEBIJAKAN MONETER DALAM MENGENDALIKAN INFLASI DI INDONESIA - Suriani suriani (Universitas Negeri Padang, 2012)
The objective of this research is to analize the effects of the variables interest rate, and exchange as one of monetary mecanisme for controlling inflation. The correlation among those variables is cointgration in the long run and short run equilibrium analyzed. In Indonesia, the monetary policy is run by monetary instruments (i.e. interest rates or monetary aggregates) to achieve price stability. This research used Unit Root Test , Cointegration Test, Granger causality and VECM (Vector Error Correction Model) Test. The results of estimation showed that have cointegration among interest rate, exchange rate and inflation in the long run. Granger causality test showed that between inflation and interest rate have no causality relationship, but for inflation and exchange rate have two directions relationship of causality. It’s means, monetary of mecanisme transmition through exchange rate channel can be good choice in making monetary policy to control inflation in Indonesia.